Study on the mechanism of action of Scutellaria barbata on hepatocellular carcinoma based on network pharmacology and bioinformatics - Yang, An-Yin; Liu, Hong-Li; Yang, Yong-Feng (Frontiers in Pharmacology, 2023)
Background: Hepatocellular carcinoma is one of the most common cancers with the characteristics of invasion and high mortality. Current forms of prevention remain severe. Scutellaria barbata is widely used in traditional Chinese medicine treatment of various tumors. This study explored the mechanism of Scutellaria barbata in the treatment of hepatocellular carcinoma by network pharmacology and bioinformatics. Methods: The active ingredients of Scutellaria barbata and potential targets for the treatment of hepatocellular carcinoma were collected by network pharmacology. The protein interaction network was constructed to screen the core targets, and the association between the core targets and diseases was further verified by bioinformatics methods. Finally, the active ingredients corresponding to the targets closely related to the disease were screened for AMDE characteristics analysis. Molecular docking of drug-like ingredients with corresponding targets was performed. We used CCK-8 kit to determine the effect of active ingredients on cell proliferation. Results : 29 candidate active ingredients and 461 related targets of Scutellaria barbata were screened. A total of 8238 potential therapeutic targets for hepatocellular carcinoma were indentified. Finally, 373 potential targets for the treatment of HCC were obtained. The active ingredients : wogonin, Rhamnazin, eriodictyol, quercetin, baicalein, and luteolin, etc. The core targets were CDK1, CDK4, SRC, and E2F1. A total of 3056 GO enrichment entries were obtained, and 180 enrichment results were obtained by KEGG pathway analysis. Genes were mainly enriched in PI3K-Akt signaling pathway, IL-17 signaling pathway, TNF signaling pathway, apoptosis pathway, and hepatocellular carcinoma pathway. Molecular docking results showed that the screened compounds had strong binding ability with the corresponding target proteins. CCK8 assays showed that Rhamnazin and Luteolin suppressed the proliferation of HCC cells significantly compared with controls. Conclusion: This study revealed that the mechanism of Scutellaria barbata in the treatment of hepatocellular carcinoma may be that the active ingredients inhibit the expression of core genes and block the PI3K-AKT signaling pathway to inhibit the proliferation, and migration and induce apoptosis of cancer cells.